The Paradox of Honesty: Catharsis, Coercion, and the Risks of Infidelity Disclosure in Marriage - Ririn Indraswari; Nurfaedah Nurfaedah (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
This study examines self-disclosure among marital infidelity perpetrators as a form of micro-level information governance crisis. It focuses on disclosure motives, decision-making processes regarding timing, mode, and content, and communication strategies used to mitigate relational disruption. Employing a qualitative case study design, data were collected through semi-structured in-depth interviews, observation, and documentation from purposively selected individuals who had disclosed infidelity to their spouses. Data were analyzed using an interactive model with iterative processes of reduction, display, and verification, supported by source triangulation. The findings reveal that disclosure is not spontaneous but reflects complex socio-emotional calculations. Two primary motives emerge: internal catharsis driven by guilt and external pressure due to potential exposure. Perpetrators employ incremental disclosure, accompanied by euphemistic and defensive narratives, to regulate conflict intensity. This process generates significant privacy turbulence and prompts boundary renegotiation, often resulting in radical transparency practices as new relational control mechanisms. Post-disclosure trajectories diverge into either relational dissolution or reconstruction. This study contributes by identifying dual-motive disclosure, conceptualizing incremental disclosure as a conflict mitigation strategy, and framing infidelity disclosure as a renegotiation of private governance. It advances sociological and governance perspectives by demonstrating that intimate information management constitutes a form of informal governance with broader social parallels.